2011
DOI: 10.1007/s00431-011-1543-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the World Health Organization criteria for chest radiographs for pneumonia diagnosis in children

Abstract: The WHO guidelines for interpretation of chest radiographs result in high level of agreement between readers for the definition of "alveolar pneumonia" and "no pneumonia" but poor agreement for non-alveolar pneumonia. The disagreement with regard to the latter was associated with overdiagnosis by pediatricians, which may lead to overtreatment. We believe that radiographic non-alveolar pneumonia should not be an endpoint for clinical trials and research, nor should it be implemented in clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 22 publications
4
46
2
2
Order By: Relevance
“…It has been recently shown among a group of 13 paediatricians and two radiologists that the main variability related to non-end-point changes [24]. Therefore the impact of heterogeneity on explaining this observed substantial reporting variability in our study is less likely.…”
Section: Discussionmentioning
confidence: 58%
“…It has been recently shown among a group of 13 paediatricians and two radiologists that the main variability related to non-end-point changes [24]. Therefore the impact of heterogeneity on explaining this observed substantial reporting variability in our study is less likely.…”
Section: Discussionmentioning
confidence: 58%
“…However, we used the WHO chest radiograph definition as it has been used in many studies evaluating various PCVs efficacy and effectiveness. Additionally, it was demonstrated that this definition has a good correlation among observers and can be used to compare results in a study with more than one investigator [39]. The chest radiograph process used in this study (pediatricians and pediatric radiologist) was similar to the one recommended by the WHO working group [10].…”
Section: Discussionmentioning
confidence: 99%
“…1 However, the standard to diagnose CaP is lacking. 2 By definition, CaP is the result of inflammation of the terminal airways (the alveoli) due to the presence of an infectious agent acquired in the community. 3 as a consequence, fluid and blood cells pass out of the blood into the alveoli and occupy the pulmonary space, which is normally filled with air.…”
mentioning
confidence: 99%